2011
DOI: 10.1074/jbc.m111.255455
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection against Traumatic Brain Injury by a Peptide Derived from the Collapsin Response Mediator Protein 2 (CRMP2)

Abstract: Background: CRMP2 is an axonal guidance protein that has been linked to NMDA receptor-mediated excitotoxicity. Results: A CRMP2 peptide protects against NMDA receptor-mediated excitotoxicity in vitro and in vivo following a traumatic brain injury. Conclusion: CRMP2 is a novel target for neuroprotection. Significance: Targeting CRMP2 could lead to development of neurotherapeutics against traumatic brain injury as well as other neuronal insults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 71 publications
4
113
0
Order By: Relevance
“…In our previous study, we had also reported that TAT-CBD3, in an activity-dependent manner, down-regulated surface expression of NR2B-containing NMDAR in dendritic spines (16). Consistent with this, in our present study, we found that TAT-CBD3 disrupts the CRMP2-NMDAR interaction (Fig.…”
Section: Crmp2 Directly Interacts With Ncx3 and Tat-cbd3 Strengthens supporting
confidence: 81%
See 4 more Smart Citations
“…In our previous study, we had also reported that TAT-CBD3, in an activity-dependent manner, down-regulated surface expression of NR2B-containing NMDAR in dendritic spines (16). Consistent with this, in our present study, we found that TAT-CBD3 disrupts the CRMP2-NMDAR interaction (Fig.…”
Section: Crmp2 Directly Interacts With Ncx3 and Tat-cbd3 Strengthens supporting
confidence: 81%
“…The immunocaptured complexes were then washed three times with lysis buffer before being heated at 70°C in equal volumes of SDS loading dye (Invitrogen). Samples were then processed by immunoblotting as described previously (5,16). Blots were probed with anti-NCX1 (NCX1 mAb R3F1), anti-NCX3 (NCX3 polyclonal antibody 95209), anti-NR2B (BD Biosciences), or anti-CRMP-2 (Sigma-Aldrich) (all 1:1000).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations